Ideal reference classroom for children and education professionals - Ariadne de Sousa Evangelista (Universidade Federal de Santa Catarina, 2020)
The main objective of this article is to understand the desires and idealizations of children and professionals regarding the space of the reference classroom in Early Childhood Education. The research used a qualitative approach, involved discussions about space, environment and place, with emphasis on Early Childhood Education. It carried the characteristics of a case study and had as research field a II pre-school classroom of a public institution in Presidente Prudente (SP). The subjects were eighteen children and the professionals who worked in the institution. The data collection procedure was the observation of space, with written and photographic record, and visual selection. The conclusions pointed out that children's wishes diverge in some respects from educators. It is also verified that the professionals have knowledge aligned with the conceptions pointed out by theorists who study the organization of the space of the institutions of Early Childhood Education, however, these knowledge are little materialized in practice.